KERUGIAN EKOLOGIS AKIBAT TINDAK PIDANA KORUPSI PADA SEKTOR LINGKUNGAN HIDUP - Putra, Rizky Tri; Sumanto, Listyowati (Ensiklopedia of Journal, 2025)
Corruption in the environmental sector constitutes an extraordinary crime that not only causes financial losses to the state but also exerts systemic impacts on ecosystems and the sustainability of natural resources. This study highlights corrupt practices related to illegal mining activities that have led to severe environmental degradation and inflicted state losses amounting to hundreds of trillions of rupiah, including ecological damages that cannot yet be conventionally quantified. The research employs a normative approach through the analysis of legislation and case studies, integrating Lawrence M. Friedman’s legal system theory and J.D. Nyhart’s theory of law and economic development to examine the interrelation between law enforcement, ecological loss, and sustainable development. The findings emphasize the importance of a multidisciplinary approach in assessing losses arising from environmental corruption and the urgent need to reform legal instruments to ensure accountability not only for financial damage but also for long-term ecological harm. This study is expected to strengthen both academic and practical arguments in advancing environmental law and combating corruption based on ecological justice in Indonesia. Keywords: environmental corruption, ecological loss, law and economics